The Impact of Phosphorus Supply on Selenium Uptake During Hydroponics Experiment of Winter Wheat (Triticum aestivum) in China - Liu, Hongen; Shi, Zhiwei; Li, Jinfeng; Zhao, Peng; Qin, Shiyu; Nie, Zhaojun (Frontiers in Plant Science, 2018)
Selenium (Se) is a necessary trace element for humans and animals, and Se fertilization is an efficient way to increase Se concentration in the edible parts of crops, thus enhance the beneficiary effects of Se in human and animal health. Due to the similarity of physical and chemical properties between phosphate (<inline-graphic xlink:href="fpls-09-00373-e001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />) and selenite (<inline-graphic xlink:href="fpls-09-00373-e002.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />), phosphorus (P) supply often significantly impacts the absorption of Se in plants, but little is known about how P supply influences the subcellular distribution and chemical forms of Se. In this study, the effects of P supply on subcellular distribution and chemical forms of Se in winter wheat were investigated in a hydroponic trial with medium Se level (0.1 mg Se L-1). P was applied with three concentrations (0.31, 3.1, and 31 mg P L-1) in the experiment. The results showed that increasing P supply significantly decreased the concentration and accumulation of Se in the roots, stems, and leaves of winter wheat. An increase in P supply significantly inhibited Se accumulation in the root cell wall, but enhanced Se distribution in the organelles and soluble fraction of root cells. These findings suggest that increased P supply inhibited the root-to-shoot transport of Se. An increase in P supply enhanced Se accumulation in the cell wall of plant stems (both apical and axillary stem) and cell organelles of plants leaves, but inhibited Se distribution in the soluble fraction of stems and leaves. This suggests that P supply enhances Se transportation across the cell membrane in shoots of winter wheat. In addition, increased P supply also altered the chemical forms of Se in tissues of winter wheat. These findings will help in understanding of the regulation grain Se accumulation and provide a practical way to enhance Se intake for humans inform Se-enriched grains.